Characterisation of a high-risk profile for maternal thrombotic and severe haemorrhagic complications in pregnant women with antiphospholipid syndrome in France (GR2): a multicentre, prospective, observational study. (December 2022) - Murarasu, Anne; Guettrot-Imbert, Gaëlle; Le Guern, Véronique; Yelnik, Cécile; Queyrel, Viviane; Schleinitz, Nicolas; Ferreira-Maldent, Nicole; Diot, Elisabeth; Urbanski, Geoffrey; Pannier, Emmanuelle; Lazaro, Estibaliz; Souchaud-Debouverie, Odile; et al.
Summary: Background: Prospective data about the risks of thrombotic and severe haemorrhagic complications during pregnancy and post partum are unavailable for women with antiphospholipid syndrome. We aimed to assess thrombotic and haemorrhagic events in a prospective cohort of pregnant women with antiphospholipid syndrome. Methods: This multicentre, prospective, observational study was done at 76 centres in France. To be eligible for this study, women had to have diagnosis of antiphospholipid syndrome; have conceived before April 17, 2020; have an ongoing pregnancy that had reached 12 weeks of gestation; and be included in the study before 18 weeks of gestation. Exclusion criteria were active systemic lupus erythematosus nephropathy, or a multifetal pregnancy. Severe haemorrhage was defined as the need for red blood cell transfusion or maternal intensive care unit admission because of bleeding or invasive procedures, defined as interventional radiology or surgery, to control bleeding. The GR2 study is registered with ClinicalTrials.gov, NCT02450396 . Findings: Between May 26, 2014, and April 17, 2020, 168 pregnancies in 27 centres met the inclusion criteria for the study. 89 (53%) of 168 women had a history of thrombosis. The median term at inclusion was 8 weeks gestation. 16 (10%) of 168 women (95%CI 5–15) had a thrombotic (six [4%] women; 95% CI 1–8) or severe haemorrhagic event (12 [7%] women; 95% CI 4–12). There were no deaths during the study. The main risk factors for thrombotic events were lupus anticoagulant positivity at inclusion (six [100%] of six women with thrombosis vs 78 [51%] of 152 of those with no thrombosis; p=0·030) and placental insufficiency (four [67%] of six women vs 28 [17%] of 162 women; p=0·013). The main risk factors for severe haemorrhagic events were pre-existing maternal hypertension (four [33%] of 12 women vs 11 [7%] of 156 women; p=0·014), lupus anticoagulant positivity at inclusion (12 [100%] of 12 women vs 72 [49%] of 146 women; p<0·0001) and during antiphospholipid history (12 [100%] of 12 women vs 104 [67%] of 156 women; p=0·019), triple antiphospholipid antibody positivity (eight [67%] of 12 women vs 36 [24%] of 147 women; p=0·0040), placental insufficiency (five [42%] of 12 women vs 27 [17%] of 156 women; p=0·038), and preterm delivery at 34 weeks or earlier (five [45%] of 11 women vs 12 [8%] of 145 women; p=0·0030). Interpretation: Despite treatment adhering to international recommendations, a proportion of women with antiphospholipid syndrome developed a thrombotic or severe haemorrhagic complication related to pregnancy, most frequently in the post-partum period. Lupus anticoagulant and placental insufficiency were risk factors for these life-threatening complications. These complications are difficult to prevent, but knowledge of the antenatal characteristics associated with them should increase awareness and help physicians manage these high-risk pregnancies. Funding: Lupus France, association des Sclérodermiques de France, association Gougerot Sjögren, Association Francophone contre la Polychondrite chronique atrophiante, AFM-Telethon, the French Society of Internal Medicine and Rheumatology, Cochin Hospital, the French Health Ministry, FOREUM, the Association Prix Veronique Roualet, and UCB.